2017
DOI: 10.2174/1874306401711010017
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of The Eosinophil and Its Measurement in Chronic Cough

Abstract: Although the aetiology of chronic cough in guidelines is clearly stated as asthma and related syndromes, gastro-oesophageal reflux disease (GORD), and upper airways disease, the inflammatory mechanisms underlying these conditions differ. Recent studies on asthma have increasingly focused on its molecular phenotypes instead of clinical characteristics. Here, we proposed the hypothesis that divides cough into two groups; the eosinophilic and neutrophilic. This division will enhance our ability to recognise the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Woerly et al ( 32 ) observed a sensitive increase in CD28 in peripheral blood eosinophils from individuals with hypereosinophilia when compared with healthy individuals, suggesting that these eosinophils may play a role not only in helminthic infections, but also in other disorders associated to allergies, when these cells are generally increased. These data may suggest the participation and activation of eosinophils in determining Th2 polarization during infectious and non-infectious pathologies ( 33 , 34 ). When analyzing the T-cells population, CD28 expression is increased in spleen and MHC-II upregulated in bone marrow upon T. canis infection, indicating productive activation of this subset during peak eosinophilia.…”
Section: Discussionmentioning
confidence: 86%
“…Woerly et al ( 32 ) observed a sensitive increase in CD28 in peripheral blood eosinophils from individuals with hypereosinophilia when compared with healthy individuals, suggesting that these eosinophils may play a role not only in helminthic infections, but also in other disorders associated to allergies, when these cells are generally increased. These data may suggest the participation and activation of eosinophils in determining Th2 polarization during infectious and non-infectious pathologies ( 33 , 34 ). When analyzing the T-cells population, CD28 expression is increased in spleen and MHC-II upregulated in bone marrow upon T. canis infection, indicating productive activation of this subset during peak eosinophilia.…”
Section: Discussionmentioning
confidence: 86%
“…It has been confirmed that numbers of active mast cells appear in the bone marrow of HES patients with a positive PDGFRA fusion gene [34]. The mechanisms underlying eosinophilic airway inflammation in chronic cough due to allergic (T helper type 2 cells) and nonallergic (innate lymphoid type 2 cells) pathways had been illustrated in 2 recent outstanding reviews [4,5]. Activated T helper type 2 or innate lymphoid type 2 cells release interleukins, causing eosinophilia inflammation, and bronchial hyperreactivity.…”
Section: Discussionmentioning
confidence: 90%
“…Sputum eosinophils are generally considered to be reliable biomarkers of Th2 airway inflammation in asthma ( 47 ). In order to perform sputum induction, the patient is required to inhale a hypertonic solution by nebulization, which helps to produce sputum that can then be expectorated ( 55 ). However, sputum induction testing has the disadvantage of not being readily available in primary care ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sputum induction’s success rate is only around 80%, due to difficulties that may arise during the sampling process ( 56 ). For instance, certain patients may experience bronchoconstriction due to the inhalation of hypertonic saline, and others may be unable to produce sufficient saliva for sputum analysis ( 55 ).…”
Section: Resultsmentioning
confidence: 99%